Reliability of one-repetition maximum test in untrained young adult men and women - Ribeiro, Alex Silva; Nascimento, Matheus Amarante do; Salvador, Emanuel Pericles; Demantova Gurjao, Andre Luiz [UNESP]; Avelar, Ademar; Ritti-Dias, Raphael Mendes; Mayhew, Jerry L.; Cyrino, Edilson Serpeloni (Ios Press, 2014)
BACKGROUND: The one repetition maximum (1RM) test is the most widely used method to analyze muscular strength. However, the 1RM reliability may be dependent on gender.OBJECTIVE: The purpose of the study was to investigate the reliability of one-repetition maximum (1RM) test in untrained young adult men and women.METHODS: Thirteen men and eleven women between 18-35 years were recruited. All subjects performed the 1RM tests in the bench press (BP), Smith machine squat (SQ), and arm curl (AC) in four sessions separated by 48 to 72 hours of recovery. At each measurement session, the subjects performed exercise-specific warm-ups and were given three attempts to reach a peak strength level for each exercise.RESULTS: There was a significant session-by-time interaction (P < 0.05) in BP and SQ, while men reached a stabilized load between sessions 2-3, women stabilized their load between sessions 1-2. Significant increases (P < 0.05) in maximal strength occurred between session 1 and 4 in BP (men = + 10.5%, women = + 13.1%), SQ (men = +17.6%, women = +20.7%), and AC (men = +7.5%, women = +11.7%).CONCLUSION: We conclude that the reliability of the 1RM tests in multiple-joint exercises may be gender dependent.
Keywords: Muscular strength; weight exercise; gender; familiarization; motor performance